LA INEFICACIA DEL CONTROL ADMINISTRATIVO ADUANERO PROPENDE AL CONTRABANDO - Masias Quevedo, Jorge Iván (2016)
In recent years a significant growth of international trade is clearly observed this growth has been even greater than the increase in production countries. Therefore, an increasing part of the production is sold in many countries internationally, and there is a greater openness and interconnection between different national economies. The importance of the socio-legal problem in the case of customs control is mainly based on the need to assist the administration of justice and to contribute to the support of customs control agencies and social control in this way to try to prevent bad habit of smuggling in border areas that exist in our country. The customs law is of great importance for commercial and fiscal policy of a country, since through it the possible protectionist measures are regulated to protect the internal market from the competition of foreign products. Our legislation allows the state through creating necessary public administration bodies to exercise the power under Art. 225 Inc. 3 of the Constitution of the Republic of Ecuador "Bodies and agencies created by the Constitution or the law for the exercise of state power, for the provision 6 of public services or to develop economic activities undertaken by the State. This research paper examines the problem of the inefficiency of customs control in our country, analyzing the reforms into national law and aspects to be considered to enhance control mechanisms aimed at improving administrative management and counteract these harmful practices for developing country. In analyzing this issue, find serious problems in the customs administration focus on eradication of smuggling, for offenders of this crime are not sanctioned as warranted Ecuadorian law for this type of customs offenses, including some processes cannot be reached issued conviction. The content of this thesis is an intellectual effort of the author in the legal, scientific and methodological level, it addresses theoretical and empirically analyzing the breach of the State, within the customs administration porsus several inefficiencies that lead to the problem of contraband into our Ecuadorian territory. Through this research we demonstrate that the Customs Administration is the agency responsible for regulating the flow of goods in the case of either import or export, in addition to imposing sanctions on persons who commit offenses to these regulations.